7a)
x - 10 + x - 11 + 3x + 6 = 180
5x -15 = 180
5x = 195
x = 39
7b)
y = 3x + 6
y = 3(39) +6
y = 117 + 6
y = 123
Step-by-step explanation:
what u suppose to do on this work, reply quickly so I can help
Answer:
There are no like terms.
Step-by-step explanation:
basically that is your answer you can not solve so it will be 3ax – 3ay – 2bx + 2by
Step-by-step explanation:
Set up the composite result function.
f(g(x))f(g(x))
Evaluate f(g(x))f(g(x)) by substituting in the value of gg into ff.
f(x2)=2(x2)−4f(x2)=2(x2)-4
Multiply 22 by x2x2.
f(x2)=2x2−4f(x2)=2x2-4